Ensuring safety for the Polish population as a task of the state on the example of the SARS-CoV-2 - Misztal-Okońska , Patrycja (Polish Journal of Public Health, 2020)
Ensuring safety for its citizens is a basic task of each country. In the past this function was limited to providing defence in the armed conflicts, while nowadays modern, highly developed countries are obliged to ensure state of safety and protection to their citizens in each situation. Apart from the natural dangers, which constantly appear depending on the season and climate of a certain area, some changes occurring in the world cause a range of new hazards. They include terrorist attacks, technical failures connected with industry development, as well as new natural dangers appearing as a consequence of climate change caused by significant human interference.  Moreover, human actions may be a reason of various catastrophes and accidents occurrence, which require fast and effective reaction of services responsible for the safety of state and citizens. In Poland the system appointed for this purpose is an emergency management system, which functions on the basis of the Act of April 26, 2007 on crisis management. Ensuring safety for the Polish population as a task of the state on the example of the SARS-CoV-2.